Dual Regulation of Sprouty 4 Palmitoylation by ZDHHC7 and Palmitoyl-Protein Thioesterase 1: A Potential Therapeutic Strategy for Cisplatin-Resistant Osteosarcoma - Tianlong Huang; Yifan Chen; Qiangqiang Zhao; Xin Wu; Hongxing Li; Xin Luo; Yang Su; Shengqun Zhang; Pan Liu; Ning Tang (Research)
Background: Osteosarcoma (OS) is a primary malignant bone tumor predominantly affecting adolescents. Chemotherapeutic agents, such as cisplatin, are commonly used in OS treatment; however, drug resistance markedly undermines treatment efficacy and contributes to reduced patient survival. The mechanisms underlying cisplatin resistance remain poorly understood. Recently, palmitoyl-protein thioesterase 1 (PPT1), a depalmitoylation enzyme, has attracted attention for its role in tumorigenesis and drug resistance. Investigating the mechanisms of PPT1 may offer new strategies to overcome resistance. Methods: This study analyzed multiple Gene Expression Omnibus datasets and utilized the OncoPredict tool to demonstrate the elevated expression of PPT1 in OS and its critical role in cisplatin resistance. By combining single-cell analysis with in vitro and in vivo experiments, we explored how PPT1 influences OS development through depalmitoylation and assessed the antitumor effects of the PPT1 inhibitor Ezurpimtrostat (GNS561), as well as its synergistic effects when combined with cisplatin. Results: We demonstrated that Sprouty 4 (SPRY4) undergoes a dynamic palmitoylation cycle regulated by zinc finger DHHC-type palmitoyl transferase 7 (ZDHHC7) and PPT1, which modulates mitogen-activated protein kinase (MAPK) signaling and subsequently affects tumor cell proliferation, migration, apoptosis, and drug resistance. Further validation confirmed the effectiveness of the PPT1 inhibitor GNS561 in overcoming cisplatin resistance. Notably, GNS561 exhibited a significant synergistic effect when used in combination with cisplatin, greatly enhancing the sensitivity of cisplatin-resistant cells. Conclusion: This study highlights the pivotal role of PPT1 in OS resistance mechanisms. PPT1 and ZDHHC7 regulate SPRY4 through a dynamic palmitoylation–depalmitoylation cycle that modulates MAPK signaling activation and contributes to OS cell proliferation, migration, and drug resistance. As a PPT1 inhibitor, GNS561 not only inhibits OS cell proliferation but also demonstrates synergistic effects with cisplatin, significantly enhancing cisplatin sensitivity in resistant cells and promoting apoptosis. Our findings offer a novel approach for targeting PPT1 in therapeutic strategies. GNS561 holds promise as an adjunctive therapy when combined with cisplatin, potentially overcoming resistance and improving efficacy, thereby enhancing the prognosis for OS patients. Future studies should further investigate the clinical potential of GNS561 and optimize OS treatment strategies.